The Legal Protection of Criminal Action on Child Addiction - Saharuddin Saharuddin; Suardi Rais; Rasty Amalia Farouk (Jurnal Daulat Hukum, 2022)
The aims of this research is the practice of abdicating responsibility and illegally claiming offspring on Child neglect. This is due to such as economic and social factors and mental illness. The law explicitly designs forms of child protection as stated in Article 5 of Act No. 23 of 2004 "every child has the right to worship according to his religion, think and express according to his level of intelligence and age under the guidance of his parents and guardians" but what happened was so many children who live on the streets due to the absence of parents as full responsibility. The long-term goal of this study is to find out specifically the causes of child neglect in Bonebolango district, as well as to explore the factors that cause a child to be neglected, this research can be achieved in the future, giving birth to benefits for all legal scientists. The research method was used in this study was empirical/sociological type of research where the researcher would go directly to the field to conduct in-depth research and assessment. The research results obtained are 1. Factors that hinder the legal protection of criminal acts of child neglect in Bone Bolango Regency based on the results of the study, namely the factors of facilities and infrastructure that are still inadequate, and law enforcers who are still considered incompetent in handling cases of child neglect so that strength is still needed. 2. The form of legal protection for the criminal act of child neglect in Bone Bolango Regency can be seen from several elements such as (not discriminating against children) which means that it does not discriminate against children.